Taxonomic revision of Etlingera (A.D. Poulsen) in Kota Kinabalu Park, Kundasang Sabah / Effaniza Binit - Binit, Effaniza (2013)
Etlingera (A.D.Poulsen) has the most species recorded (16) in Kinabalu Park rather than the other 7 genera in the tribe Alpinieae A. Rich; 6 species of Alpinia, 11 species of Amomum, 5 species of Plagiostachys, and 1 species of Elettariopsis, Elettaria and Geocharis respectively. The purpose of the study was to revise the collection of Deposited Specimen Vouchers (DSV) of Etlingera species in Kinabalu Park. This study was done following standard taxonomic procedures involving grouped DSV into taxa, and developed a dichotomous key. There were 16 species out of 40 Etlingera species of Borneo which found in Kinabalu Park which represented by 135 DSV. These include Etlingera amomoides (A.D.Poulsen & Mood), Etlingera elatior (Jack) R.M. Smith, Etlingera pyramidosphaera (K.Schum) R.M.Smith, Etlingera pubescens (R.M.Smith), Etlingera brevilabrum (Valeton) R.M.Smith, Etlingera velutina (Ridl.) R.M Smith, Etlingera megalocheilos (Griff.) A.D.Poulsen, Etlingera rosamariae (A.D.Poulsen & Gobilik), Etlingera baculutea (A.D.Poulsen & H.Ibrahim), Etlingera sessilanthera (R.M.Smith), Etlingera coccinea (Blume) S.Sakai & Nagam, Etlingera cf. nasuta (K.Schum) R.M.Smith, Etlingera corrugata (A.D.Poulsen & Mood), Etlingera fimbriobracteata (K.Schum) R.M.Smith, Etlingera longipetiolata (B.L.Burtt & R.M.Sm), and Etlingera sayapensis (A.D.Poulsen & H.Ibrahim). The 38 DSV of unknown Etlingera species were belonged to the 9 identified species which were E. coccinea (Blume) S.Sakai & Nagam, E. fimbriobracteata (K.Schum.) R.M.Smith, E. longipetiolata (B.L.Burtt & R.M.Smith), E. megalocheilos (Griff.) A.D.Poulsen, E. pubescens (R.M.Smith), E. pyramidosphaera (K.Schum.) R.M.Smith, E. rosamariae (A.D.Poulsen & Gobilik), E. sessilanthera (R.M.Smith) and E. velutina (Ridl.) R.M.Smith. Most of the DSV identified as E. rosamariae (A.D.Poulsen & Gobilik) by a diagnostic character midrib above pale brown and lamina obovate. The DSV key of Etlingera (A.D.Poulsen) to the species was made mainly on the basis of macro-morphological characters.